Gente como uno : class, belonging, and transnationalism in Jewish life in Lima - Yalonetzky, Romina, 1980- (Jewish Latin American studies., 2021)
"In San Isidro, Lima, the only Jewish school in Peru stands on a street widely known as "Los Manzanos" ("The Apple Trees") but whose name changes to "Maimonides" (the Jewish sage) depending on which sign you look at. As she takes us on a stroll through this six-block street and its different names, Dr. Romina Yalonetzky introduces readers to a physical microcosm of the intersection between Peruvian and Jewish identity, elucidated through the varied voices and experiences of Peruvian Jews. This book presents a unique understanding of Jewish Peruvian-ness and in so doing sheds a novel light on both Jewish and Peruvian identities"--